Peningkatan Substansi Penelitian Bahasa dan Sastra Bagi Dosen Bahasa Indonesia FKIP Jabal Ghafur - Ramli; Armia; Muhammad Idham; Nurrahmah; Teuku Alamsyah (Yayasan Kawanad, 2024)
Community service aims to enhance the substance of research in the field of language and literature for Indonesian language lecturers at the Faculty of Teacher Training and Education (FKIP), Jabal Ghafur University. The project is implemented by involving lecturers as change agents leading community engagement activities and engaging the local community. Strategic steps include enhancing the research capacity of lecturers, providing training, and developing educational and literacy programs in the community. Through training sessions and workshops, Indonesian language lecturers are empowered to adopt innovative research methods relevant to the developments in language and literature. Additionally, they actively participate in initiating literacy and language programs that directly benefit the local community, such as writing workshops, language lectures, and creative literacy activities. The results of this community engagement show a significant improvement in the quality of research and literacy activities among Indonesian language lecturers. Lecturers are able to integrate their research findings into curriculum development and teaching materials, thereby positively impacting student learning. Furthermore, community literacy activities contribute significantly to enhancing understanding and appreciation of language and literature at the community level. This community service not only enhances the competence of lecturers but also encourages the transfer of knowledge and skills to the community. The project can serve as a model for the development of similar activities in various communities, providing sustainable benefits in enhancing the substance of language and literature research at the local level.